Pengaruh Motivasi, Gaya Kepemimpinan, Pelatihan dan Teamwork Terhadap Kinerja Pegawai BPJS Ketenagakerjaan Bengkulu - Muhammad Ajid Ajid (STIE AMKOP, 2023)
This study aims to determine the magnitude of the influence of motivation, leadership style, training and teamwork on employee performance at the Bengkulu City Employment BPJS. The method used in this study is a quantitative method. The population and sample in this study were all employees of the Bengkulu City Employment BPJS, totaling 31 people. The results of this study conclude that the motivational variable has a significant effect on employee performance, the leadership style variable has a significant effect on employee performance, the training variable has a significant effect on employee performance, the teamwork variable has a significant effect on employee performance and the variables motivation, leadership style, training and teamwork all have an effect on employee performance.